2022
DOI: 10.1002/vms3.1039
|View full text |Cite
|
Sign up to set email alerts
|

Copromicroscopic study of gastrointestinal parasites in captive mammals at Central Zoo, Lalitpur, Nepal

Abstract: Background Zoological gardens (Zoo) provide abode to various threatened animals or trafficked animals seized by the authorities, and injured and orphaned animals. Captive animals are more susceptible to infection as they are under significant stress due to diet and space which further dwindle their resistance to parasitic infections. Objectives This study was conducted to determine the prevalence and burden of gastrointestinal parasites in captive mammals housed at Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
2
10
0
Order By: Relevance
“…Amphibia can be infected by multiple species of Eimeria, Isospora and Goussia , and in Pisces several species of Eimeria and also Goussia may occur ( Schnieder 2006 ). However, in this study, coccidia were detected most frequently in the order Artiodactyla (34.6%) followed by Rodentia (10.5%), Marsupialia (9.4%) and Carnivora (8.1%) which is in accordance with Dhakal et al (2023) and Pérez Cordón et al (2008) who also found coccidia most prevalent in Artiodactyla at 34.28% and 31.8%, respectively. In our study, ruminants (Moschidae and Bovidae) were most frequently infected with coccidia.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Amphibia can be infected by multiple species of Eimeria, Isospora and Goussia , and in Pisces several species of Eimeria and also Goussia may occur ( Schnieder 2006 ). However, in this study, coccidia were detected most frequently in the order Artiodactyla (34.6%) followed by Rodentia (10.5%), Marsupialia (9.4%) and Carnivora (8.1%) which is in accordance with Dhakal et al (2023) and Pérez Cordón et al (2008) who also found coccidia most prevalent in Artiodactyla at 34.28% and 31.8%, respectively. In our study, ruminants (Moschidae and Bovidae) were most frequently infected with coccidia.…”
Section: Discussionsupporting
confidence: 85%
“…It has been suggested that the simplicity of their lifecycle, as they do not need an intermediate host and some of them are immediately infective after excretion, contributes to a parasitic infection. Moreover, the high environmental tenacity of excreted stages, low infection doses and short prepatent periods make transmission very effective, especially in confined spaces ( Levecke et al, 2007 ; Dhakal et al, 2023 ). This may also be the case for the parasites found in this study, as the protozoans (e.g., coccidia , Cryptosporidium spp.)…”
Section: Discussionmentioning
confidence: 99%
“…The significant finding of a considerable range of GI parasitic infections (62.6% of animals infected) among captive mammals at Khon Kaen Zoo raises concerns. Comparable prevalence values have been reported from zoo populations in other countries, such as Nepal (19.5%) [ 33 ], Malaysia (56.3%) [ 34 ], and Bangladesh (60.5%) [ 35 ]. Higher prevalence has been reported in some cases, such as 68.3% in the Rio de Janeiro Zoo [ 36 ], 72.5% in Spain [ 5 ], and 71.8% and 74.2% in Brazil [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 54%
“…In other comparative studies between zoos [ 34 , 104 ], differences among centres were attributed to the type of facility, the possibility of herbivore grazing, and the frequency of faeces collection and cleaning. Other important factors include possible water or food contamination (animal carcasses for carnivores, grass and herbaceous material for herbivores) [ 37 , 113 , 114 ]. In the present study, control over water and food provided to the animals is similar in both zoos, so the differences in the observed results between them must have another origin.…”
Section: Discussionmentioning
confidence: 99%